Real-time macroeconomic data and uncertainty - Katharina Glass; Ulrich Fritsche (Hamburg University, Department Socioeconomics, 2015)
Most macroeconomic data is continuously revised as additional information becomes available. We suggest that revisions of data is an increasingly important source of uncertainty about the state of the economy and offer an alternative channel of uncertainty - data uncertainty. This paper adds on the uncertainty literature and focuses on data uncertainty, which originates in the revision structure of data. We find that apart from the general and economic policy uncertainty, the data uncertainty has been rising throughout the past decade in the US and Euro area. To the best of our knowledge, this is the first study of Euro area data uncertainty. Our analysis shows that there is a positive lagged effect of economic policy uncertainty on data uncertainty for both regions. Our finding corresponds to the recent literature on increased macroeconomic and economic policy uncertainty during and after the "Great Recession".
Older version: http://hdl.handle.net/10419/103201
Keywords: C53; C8; D80; E3; 330; forecasting; information content; uncertainty; revisions; revision errors; entropy; signal-to-noise ratio; integrated signal-to-noise ratio; recession; EPU; VSTOXX; VIX